2016
DOI: 10.18632/oncotarget.6884
|View full text |Cite
|
Sign up to set email alerts
|

Expression of programmed cell death-ligand 1 and its correlation with clinical outcomes in gliomas

Abstract: Programmed cell death-ligand 1(PD-L1) was expressed in various malignancies, and interaction with its receptor programmed cell death 1 (PD-1) often contributed to immune evasion of tumor cells. In this study, we explored the expression of PD-L1 and its correlation with clinical outcomes in gliomas.Clinicopathological data of 229 patients with gliomas was collected. PD-L1 expression was assessed by tissue-microarray-based immunohistochemistry. Over 5% of tumor cells with cytoplasm or membrane staining was defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 48 publications
3
40
4
2
Order By: Relevance
“…c Kaplan-Meier survival curve for patients with high-grade gliomas (n = 100).Overall survival rate in patients with high expression of WTAP in glioma was significantly lower than in patients with low expression of WTAP. (log rank test P < 0.001) Zeng et al 2016). In our study, besides age and WHO grade, WTAP expression was showed closely associated with overall survival and to be an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 60%
“…c Kaplan-Meier survival curve for patients with high-grade gliomas (n = 100).Overall survival rate in patients with high expression of WTAP in glioma was significantly lower than in patients with low expression of WTAP. (log rank test P < 0.001) Zeng et al 2016). In our study, besides age and WHO grade, WTAP expression was showed closely associated with overall survival and to be an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 60%
“…In a study of 229 glioma (grades I–IV) patients, Zeng et al [17] found no significant associations between PD-L1 expression and OS. Using the median survival time (12 months) as a cut-off point, these authors found that a high level of PD-L1 expression was significantly associated with the poor OS of patients who survived and were followed up over 12 months.…”
Section: Pd-l1 Expression and Prognosis Value In Gliomasmentioning
confidence: 99%
“…Ultimately, 4 articles were included in this meta-analysis (Fig. 1) 912 .
Figure 1Flow diagram of the literature search and study selection protocols.
…”
Section: Resultsmentioning
confidence: 99%
“…9 DenmarkProteinGlioblastomaNMIFCNANon-percentage ¶ 176/1135.29UA4.67 (1.42–15.43)6Berghoff, A. S. 11AustriaProteinGlioblastomaFFPEIHCMembranousPercentage (≥5%)11744/7337.61UA1.22 (0.83–1.8)7GeneGlioblastomaTCGAAgilent microarrayMedian PD-L1 expression levels446223/22350MA1.036 (0.87–1.23)Nduom, E. K. 15 † USAProteinGlioblastomaTMAIHCMembranesPercentage (≥5%)9458/3661.70UA1.74 (1.09–2.77)7GeneGlioblastomaTCGAIllumina RNASeq0.37149NMNMMA1.52 (1.03–2.25)Zeng, J. 12 ChinaProteinGliomaTMAIHCMembranes/CytoplasmPercentage (≥5%)229117/11251.09UA1.05 (0.76–1.47)8Note: † This research contains two cohorts, one is protein cohort, and the other is gene cohort. § Cut off criterion for PD-L1 Positive. ¶ >10 cells/field tumor cells. # HR for OS and positive PD-L1 expression.Abbreviations: IHC, Immunohistochemistry; IFC, Immunofluorescence histochemistry; FFPE, Formalin-fixed paraffin-embedded; TMA, tissue microarray; TCGA, The Cancer Genome Atlas.UA, univariate analysis; MA, multivariate analysis; HR, Hazard ratio; CI, Confidence interval; NM, Not mentioned; NOS, Newcastle-Ottawa scores. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation